Deciphering fruit sugar transport and metabolism from tolerant and sensitive tomato plants subjected to simulated field conditions. Issue 4 (21st February 2021) - Lopez‐Delacalle, Maria; Camejo, Daymi; Garcia‐Marti, Maria; Lopez‐Ramal, Maria Jose; Nortes, Pedro A.; Martinez, Vicente; Rivero, Rosa M.
Abstract: In the current state of climate change, we must assume that abiotic stresses act together under natural field conditions, these will increase in the coming years. Therefore, in this report we investigated how sugar metabolism was affected under simulated field conditions, where plants faced high ambient temperatures and a low‐quality water irrigation. Our studies were carried out on fruits of two tomato recombinant lines, a tolerant and a sensitive one exposed to the combination of heat and salinity. Two ripening stages (mature green and red ripe fruits) were used in our analyzes, where the gene expression levels of the main biosynthetic genes and transporters, enzymatic activities and compounds related to the synthesis, accumulation, and degradation of sugars in plants were analyzed. The tolerant line showed highly significant differences in red ripe fruits in comparison to the sensitive one under the simulated field conditions (35°C + 60 mM NaCl), with an overexpression of the genes SlFBP, SlSPS, SlSUS3, and SlNi . These expression patterns correlated with a higher activity of the enzymes FBP, SPS, SUS3, AI, and G6PDH, which resulted in the accumulation of fructose, glucose and UDP‐glucose. Our results showed the advantage of using tomato recombinant lines for rescuing important traits, such as the resistance to some abiotic stresses, and for the identification of important molecular and metabolic markers that could be used to determine fruit quality in green or red maturity stages under detrimental environmental field conditions.